English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2 y (squared) - y = 6

2006-12-08 02:40:53 · 9 answers · asked by James B 1 in Science & Mathematics Mathematics

9 answers

1. divide the entire equation by 2.
= y^2 - .5y = 3
2. using completion of the square, notice that (y - .25)^2 = y^2 - .5y + .25^2, so from this, add .25^2 to both sides
3. equation reads (y - .25)^2 = (49/16)...take square root of both sides to get (y - .25) = +or- (7/4)
4. add .25 to both sides to achieve answer as y = 2 or (-3/2)

2006-12-08 02:51:08 · answer #1 · answered by goldeneye2131 2 · 0 0

Step one, subtract 6 from both sides of the equation:
2y (squared) - y - 6 = 0.
We now have a quadratic trinomial. You can use the quadratic formula, or if you're slick, deduce the two binomials that can be multiplied together to get 2y (squared) - y - 6.
See that it would have to have this form:
( 2y +/- ... )( y +/- ... ).
See that the constant terms (represented there-above by the "...") will either be 1 and 6, 6 and 1, 2 and 3 or 3 and 2.
You'll need to try each one to see which gives you 2y (squared) - y - 6.
Only with practice can you immediately see the binomials are:
( 2y - 3 )( y + 2 )
So we have:
( 2y - 3 )( y + 2 ) = 0
This means ( 2y - 3 ) = 0
or ( y + 2 ) = 0
Hence y = 3/2 or y = -2.
Feel free to email me for any clarifications :)

2006-12-08 10:52:59 · answer #2 · answered by Bugmän 4 · 0 0

Hello
2y^2-y = 6
The above is
a quadrtic euation in nonstandard form
the first step is to rewrite the equation in standard
2y^2 - y - 6 = 0
(do the above by moving the number 6 to the left side of the equal sign )
step 2
factor the equation
2 (y - 3 )(y + 2 )
step 3
set the equation inside the parantsesis to 0

( y - 3 ) = 0 ( y + 2 ) = 0
+ 3 +3 - 2 - 2
y = 3 y = -2
the solution is :

{ 3 , -2 }

2006-12-08 11:28:50 · answer #3 · answered by Anonymous · 0 0

2y^2-y-6=0
now,we have to find two nos for which the sum = -1(coefficient of y) and product = -12(product of constant -6 and coefficient of y^2);Let us see first two nos for which product is -12
here are the possibilities:
1.)-1and 12 or -12 and 1
2)-2 and 6 or 2 and -6
3)-3 and 4 or 3 and -4
Now if you look at the above possibilities the one satisfying the above condition is -4 and 3.
sum:= -4+3 = -1
product = -12

so the equation becomes
2y^2 -4y + 3y -6 =0
now taking factors common we have

2y(y-2) +3(y-2) =0
Taking y-2 common we have
(2y+3)(y-2) = 0
therefore y =2 or -3/2
now if you substitute any of these nos in your equation this will satisfy your equation.
Hope this answers your question

2006-12-08 11:02:12 · answer #4 · answered by PASUMARTY S 1 · 0 0

Sure!

2y^2 - y -6 = 0 is a quadratic equation. You can use the quadratic formula: http://en.wikipedia.org/wiki/Quadratic_formula

Or factor by inspection:

(2y + 3) * (y - 2)=0

y= -1.5 or 2

Done!

2006-12-08 10:46:20 · answer #5 · answered by Jerry P 6 · 0 0

just plug in numbers for y to try and solve.

Start with 1

2(1)sq - 1 = 6?
2-1=6 no

try 2

2(2)sq -2 = 6?

8-2=6? yes!

answer is 2

2006-12-08 10:46:20 · answer #6 · answered by romasuave1 2 · 0 1

2y^2 - y =6 set up quadradic....
2y^2 - y -6 =0 .....factor ......
(2y+3) (y -2)

y-2=0 .... y=2
2y-3=0 ......y = -3/2

when x=2.......2(4) - 2 = 6 ok

when x=3/2.... 2(9/4) - (-3/2) = 18/4 - (-6/4) = 24/4 = 6 ok

2006-12-08 11:03:48 · answer #7 · answered by Brian D 5 · 0 0

2 y (squared) - y = 6
2y^2-y=6
2y^2-y-6=0
(2y+3)(y-2)=0
(2y+3)=0
y =-3/2
and
(y-2)=0
y=2

therefore, two answers...when y=-3/2 and when y=2

2006-12-08 10:48:51 · answer #8 · answered by angel 2 · 0 0

2Y^2-Y-6=0
2Y^2-4Y+3Y-6=0
2Y(Y-2)+3(Y-2)=0
(Y-2)(2Y+3)=0
Y-2=0 2Y+3=0
Y=2 Y=-3/2

2006-12-08 10:55:29 · answer #9 · answered by SHAILY 1 · 0 0

fedest.com, questions and answers